QUALITY MANAGEMENT IN THE INDUSTRY: A Comprehensive View of PDCA - Adriana Pires Simões, Thaís; Ferrarezi Junior (Revista Interface Tecnológica, 2025)
This qualitative study analyzed the impacts of implementing the PDCA Cycle in the fishery and automotive industries. In the fishery industry, PDCA implementation resulted in a 25% improved operational efficiency, leading to a 15% reduction in production costs. Additionally, a 30% increase in compliance with food safety standards and a 20% decrease in generated waste were observed, promoting more sustainable practices. In the automotive sector, the productive environment capacity increased by 18% after the implementation of PDCA, with a decrease of 22% in the defect rate, resulting in a 10% reduction in costs associated with rework and warranty. Furthermore, a notable 15% increase in customer satisfaction, measured through post-sales surveys, was observed. These quantified results highlight the tangible benefits of implementing the PDCA Cycle in both sectors, demonstrating its measurable effectiveness in operational efficiency, product quality, and customer satisfaction. This numerical focus provides a clear understanding of the specific benefits of PDCA in different industrial contexts, offering a solid foundation for the practical application of this methodology. Additionally, this work introduces numerical data, enhancing its qualitative nature. The study encompasses an introduction, theoretical framework, methodology, objectives, and final considerations, providing a comprehensive exploration of the PDCA Cycle’s impact on industrial management.